Geomatica e telerilevamento per le fasce tampone di vegetazione lungo i corsi d'acqua - Biscontini, Daniele; Monaldi, Giulio; Tosi, Paolo; Rossi, Livio (GEOmedia, 2012)
La salvaguardia del territorio europeo è uno degli obiettivi della cosiddetta ‘Condizionalità Agro-ambientale' che mira a diffondere l'uso corretto e illuminato di buone pratiche agricole che, nell'ottica dei nuovi requisiti, sono indirizzate alla protezione dei corsi d'acqua attraverso tecniche geomatiche. Geomatics and remote sensing for watershed characterization This paper faces criteria definition for water streams identifica-tion, application areas, different risk zones, buffer width, effi-ciency indicators, through: existing data, new Remote Sensing products and Geomatic tools for watersheds characterization. The project target is a shared information, both for methodol-ogy and homogeneous farmer commitments at national/EU level, using validated layers/data, at contained costs.